Centering caregiver voices on caregiving needs of children with neurodevelopmental disorders in low-resource settings - Tamara Chansa-Kabali; Martha Banda-Chalwe; Joseph Lupenga (PLoS ONE, 2025)
Caregivers of children with neurodevelopmental disorders (NDDs) in low-resource settings face significant challenges in accessing appropriate care, support, and interventions. This study was centred on caregivers’ lived experiences as a channel through which research and intervention planning draws a better understanding of experiences, barriers, and needs for providing care. Using qualitative methods, we applied the interpretive phenomenological approach to navigate caregiving needs required to optimise the caregiving experience. Findings reveal that caregivers navigate multiple hardships, including limited knowledge and care skills on NDDs, access to rehabilitation services, and heightened social stigma exemplified through lack of empathy in families and communities. Despite these challenges, caregivers demonstrate remarkable resilience and develop adaptive strategies to support their children’s development by identifying ways that empower caregiving—increased knowledge, use of rehabilitation services in community spaces, empathy and thriving together through support groups. By centering on caregiver perspectives, this research informs more inclusive and sustainable approaches to supporting families of children with NDDs in resource-constrained environments.